PENGARUH BAKTERI DALAM PENCEMARAN LIMBAH TERHADAP KOROSI PADA STRUKTUR BAJA DI LINGKUNGAN LAUT - Herman Pratikno (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2007)
Corrosion is the phenomena on the offshore structures which is impossible to avoid. Corrosion is occurred by physical, chemical and biological process. Generally, biological corrosion is caused by presence of microbes which on its process can be individual or make a new colony with other bacteria. Ocean outfall usually produce some bacteria which having role in corrosion process. With artificial sea water media and the corrosion rate calculation based on ASTM standard, has been compare the corrosion rate of the specimen on 3 sea water condition, consist of deep sea water (salinity 33‰), medium sea water (salinity 35‰), shallow sea water (salinity 37‰) and variate into 3 kinds bacteria as follows: Escherichia coli, Pseudomonas fluorescens, and Thiobacillus ferroxidans The result of this analysis show that maximum corrosion rate is 1,321 mm/year or increase 89,79% from the normal condition without adding bacteria, with value 0,696 mm/year.